PENERAPAN SISTEM PEMERINTAHAN INDONESIA DITINJAU DARI PENDEKATAN BERBASIS TEORI MAUPUN PRAKTIK - Cut Novisar Syahfitri; Irfan Setiawan; Nurul Khoiriah Putri (Jurnal Ilmiah Administrasi Pemerintahan Daerah, 2021)
Indonesia implements a presidential-based system so that it is found that the division of power that exists in Indonesia consists of power known as executive power, power known as legislative power, to judicial power to create a balance that exists in Indonesia. All the rules that have been determined can be found in a constitution, but efforts are needed to perfect them, especially with regard to rules to limit a power and policy so that executive power, legislative power, to judicial power can be implemented effectively and efficiently. The method used in this research is the normative method. The purpose of using this method is for the author to carry out an analysis to compile a discussion using a variety of existing theories and carry out practice using the object of implementing the existing government system in Indonesia. Based on the value of policy theory, an institution in Indonesia uses a government system known as presidential, but in reality there is no evidence that Indonesia uses a presidential system when viewed from the power possessed by the Indonesian state. If viewed from the system used, it can be seen that Indonesia applies a system to divide a power that applies in the Indonesian state. This article presents proposals related to suggestions for improving the Indonesian government system from concepts to practices that are implemented efficiently.